Fully recyclable carbon fiber reinforced vanillin-based epoxy vitrimers. (5th January 2022) - Wang, Yuli; Jin, Bihui; Ye, Dezhan; Liu, Zengjin
Graphical abstract: Highlights: Chemically Recyclable vanillin based epoxy vitrimers were achieved. The mechanical properties were comparable to those of Bisphenol A epoxy/CF composites. Carbon fiber could be recycled at 25 °C for 2 h under 0.1 M HCl/DMF (v/v = 1/1) The surface morphology and chemical structure of carbon fiber are not changed. Abstract: Fabrication of recyclable and reprocessable epoxy vitrimers is opening more application opportunities for carbon fiber (CF) recycling. Despite the extensive study of epoxy thermosets from lignin-based monomer of vanillin, however, few works have been focused on its vitrimers, let alone their mechanical, interfacial, solvent resistance and fully recyclable properties of vanillin-based epoxy vitrimers /CF composite. Here the effect of four types of curing agents on the above properties has been carefully studied. Two-layer CF reinforced vanillin-based epoxy vitrimers composites that was cured with Isophoronediamine shows higher tensile strength at break and Young's Modulus than those of Bisphenyl A epoxy (E51)/CF and other epoxy vitrimers/CF composites, which reaches 571 MPa and 11.7 GPa, respectively. All vanillin-based epoxy vitrimers are easily degradable at room temperature in acid solution except for that cured with 4, 4′-Diaminodiphenylmethane. The surface morphology and chemical structure of CF are not altered after degradation. Importantly, completely recyclable vanillin-based epoxy vitrimers are achieved by imine exchange reaction; however, the mechanical and thermal properties of it are slightly inferior to the origins. This work demonstrates that the mildly degradable, fully recyclable vanillin-based epoxy vitrimers and readily recycling of CF are desirable for the development of lignin based functional materials.